Success Factors That Affect The Best Practices For EProcurement In Small And Medium Public And Private Firms In Malaysia: An Actor Network Theory Perspective - Mohamed Fathi Alaweti
Electronic procurement (eProcurement) refers to the e-government systems use of information and communication technology (ICT) to facilitate transactions processing of goods and services. EProcurement best practices are difficult to identify. Hence, enterprises have tried to find success factors that gain the benefits of eProcurement in order to cut cost, process streamlining, improved contract compliance and improve management. However. many challenges stood in the way avoiding enterprises to take full advantage of eProcurement best practice. This study aim to identify success factors that affect the best practices of eProcurement in small and medium public and private firms (SMPPs) in Malaysia from an actor network theory (ANT) perspective. The research has employed qualitative data collection and analysis. Interviews were conducted at 6 case studies. Eleven supplier's companies and nine buyer's companies that listed on the main board of Bursa Malaysia participated in this research. Two forms of analysis were conducted: within-case analysis and cross-case analysis. Based on the interviews analysis, nine factors were found as success factors for eProcurement best practices, which are Organizational Culture, Organizational Structure, Organizational Developments, Leadership and Quality, Leadership and Implementation, Computer Self-Efficacy, Products Efficiency, Security and Technology Adoption. This research shows that ANT theory can be used to understand the eProcurement processes and as a lens to identify the success factors. Nevertheless, this research focused only on small and medium public and private organizations that use eProcurement as a platform of processing purchasing transactions.